1983
DOI: 10.1099/0022-1317-64-1-127
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Murine Coronavirus RNA by Hybridization with Virus-specific cDNA Probes

Abstract: SUMMARYGenome RNA of mouse hepatitis virus (MHV) strain A59 has been used as a template to synthesize two virus-specific probes: cDNA~ep, representing the majority of sequences of the genome RNA and cDNAy, representing the 3' end of the genome RNA. Molecular hybridization with these cDNAs was used to characterize both genome RNA and intracellular virus-specific RNAs. Hybridization of genome RNAs of MHV strains A59, JHM, and MHV-3 with A59 cDNArep showed that, although these three strains exhibit different path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…We observed a uni- form deletion of approximately 1.5 X 1 O5 Da from the E2 glycoprotein and higher molecularweight subgenomic mRNAs of ATllf cord virus when compared with ATllf and ATlIe brain viruses. Because the E2 mRNA was the lowest molecular weight mRNA with a deletion and because of the nested set arrangement of the coronavirus mRNAs (Stern and Kennedy, 1980a,b;Cheley et al, 1981 a;Weiss and Leibowitz, 1983) one can conclude that the deletion occurred in the coding region of the E2 glycoprotein mRNA of the ATIIf cord virus. The genomic size RNA from wild-type JHM and JHM variants appeared to comigrate (Fig.…”
Section: Comparison Of Mrna and Proteins Synthesized By Jhm Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a uni- form deletion of approximately 1.5 X 1 O5 Da from the E2 glycoprotein and higher molecularweight subgenomic mRNAs of ATllf cord virus when compared with ATllf and ATlIe brain viruses. Because the E2 mRNA was the lowest molecular weight mRNA with a deletion and because of the nested set arrangement of the coronavirus mRNAs (Stern and Kennedy, 1980a,b;Cheley et al, 1981 a;Weiss and Leibowitz, 1983) one can conclude that the deletion occurred in the coding region of the E2 glycoprotein mRNA of the ATIIf cord virus. The genomic size RNA from wild-type JHM and JHM variants appeared to comigrate (Fig.…”
Section: Comparison Of Mrna and Proteins Synthesized By Jhm Variantsmentioning
confidence: 99%
“…x 1 O6 Da mRNA designated mRNA 7; the genomic size mRNA is called mRNA 1 (Spaan et al, 1981;Wege et a/., 1981). The mRNAs form a 3'-coterminal nested set extending for different lengths in a 5' direction (Stern and Kennedy, 1980a,b;Cheley et al, 1981a;Lai and Stohlman, 1981;Leibowitz et al, 1981;Spaan et al, 1983;Weiss and Leibowitz, 1983). The 5' end of each mRNA not present in smaller mRNA species contains the coding sequence utilized during the infection (Leibowitz et al, 1982;.…”
Section: Introductionmentioning
confidence: 99%
“…Infected cells contain five or six subgenomic mRNAs, depending upon the virus studied, and an RNA species which is indistinguishable from genome RNA in structure (Leibowitz et al, 1981;Stern and Kennedy, 1980a, b;Lai et al, 1981). Structural studies have established that the subgenomic mRNAs make up a "nested set" with coterminal 3' ends (Leibowitz et a/., 1981;Stern and Kennedy, 1980a, b;Lai et a/., 1981;Cheley et a/., 1981;Weiss and Leibowitz, 1983;Spaan et al, 1982) and contain a leader sequence of approximately 72 bases at their 5' termini (Spaan et a/., 1983;Lai et a/., 1983Lai et a/., , 1984. This is shown schematically in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotropic MHV-4 strain showed the highest degree of difference among the strains tested, which also included MHV-2, 3 and A59 (Wege et al, 1981;Weiss and Leibowitz, 1983). Hybridization studies with cDNA clones of the viral RNAs revealed extensive nucleic acid homologies between MHV strains (Cheley et al, 1981;Weiss and Leibowitz, 1983). More recently sequence analyses of the N gene indicated an overall 94% homology between the strongly neurotropic MHV-4 and the weakly neurotropic MHV-A59 (Armstrong et al, 1983;Skinner and Siddell, 1983).…”
mentioning
confidence: 99%
“…In similar analyses with other strains, each MHV isolate yielded a unique oligonucleotide pattern. The neurotropic MHV-4 strain showed the highest degree of difference among the strains tested, which also included MHV-2, 3 and A59 (Wege et al, 1981;Weiss and Leibowitz, 1983). Hybridization studies with cDNA clones of the viral RNAs revealed extensive nucleic acid homologies between MHV strains (Cheley et al, 1981;Weiss and Leibowitz, 1983).…”
mentioning
confidence: 99%